Blood picture and phagocytosis in immunised BALB/c mice with the lipopolysaccharide extracted from Klebsiella pneumoniae against infection with secondary hydatid disease - Asmaa Abdulaziz Ali; Ibrahim Ali (College of Education for Pure Sciences, 2010)
ABSTRACT The study tested the effect of the lipopolysaccharide, which was extracted from Klebsiella pneumoniae, on immune response of BALB/c mice infected with secondary hydatid disease caused by experimental infection with Echinococcus granulosus protoscolices. The immunopathological changes accompanied with secondary hydatid disease in mice treated with LPS were followed in comparison with the positive and negative control group along 3-5 months period of the experiments. Criteria taken into consideration included the changes in the total and differential count of WBCs, and non-specific (innate) immune response, expressed by the change in the phagocytic index. Results of the present study revealed an increase in the means of total and differential count of WBCs, expressed by increase in the number of lymphocytes accompanied by a decrease in number of monocytes, neutrophils and eosinophils in treated mice. An increase in the nonspecific immune responses is represented by increase in the mean of phagocytic index. Therefore, it may be concluded that the lipopolysaccharide extracted from Klebsiella pneumoniae can be used as a non-toxic stimulator of non-specific immunity against infection with secondary hydatid disease.